2020
DOI: 10.51791/njap.v47i4.62
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric characteristics of Red Sokoto and Sahel goats in Maigatari Local Government Area of Jigawa State

Abstract: The initial step involved in any animal genetic improvement program is to describe the morphometric traits considered. Therefore, a study was conducted in Maigatari Local Government Area of Jigawa State to determine some morphometric characteristics of Red Sokoto and Sahel goats. A total of 250 goats (187 Red Sokoto and 63 Sahel) of mixed sex and age were used for the study. The animals were sampled from Maigatari main livestock market. Data generated were subjected to simple descriptive, analysis of variance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
6
3
0
Order By: Relevance
“…Similarly, for estimating the live body weight of sheep and goats, several researchers have recommended using solely heart girth, owing to ease of use for field animals (Kumar et al, 2018; Mayaka et al, 1996; Mohammed & Amin, 1996; Myeni & Slippers, 1997; Nsoso et al, 2003; Ravimurugan et al, 2013, Singh et al, 2020; Slippers et al, 2000; Topai & Macit, 2004). In accordance with our findings, Adamu et al (2020), Adeyinka and Mohammed (2006), Kumar et al (2021), Fajemilehin and Salako (2008), Pesmen & Yardimci (2008) and Yilmaz et al (2013) suggested the use of both body length and heart girth as the most appropriate metrics for predicting live body weight.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, for estimating the live body weight of sheep and goats, several researchers have recommended using solely heart girth, owing to ease of use for field animals (Kumar et al, 2018; Mayaka et al, 1996; Mohammed & Amin, 1996; Myeni & Slippers, 1997; Nsoso et al, 2003; Ravimurugan et al, 2013, Singh et al, 2020; Slippers et al, 2000; Topai & Macit, 2004). In accordance with our findings, Adamu et al (2020), Adeyinka and Mohammed (2006), Kumar et al (2021), Fajemilehin and Salako (2008), Pesmen & Yardimci (2008) and Yilmaz et al (2013) suggested the use of both body length and heart girth as the most appropriate metrics for predicting live body weight.…”
Section: Resultssupporting
confidence: 91%
“…We observed similar estimates of means of body measurements in literature (Dudhe et al, 2015;Nsoso et al, 2004;Singh et al, 2020). Higher estimates (Abd-Allah et al, 2019;Pesmen & Yardimci, 2008) and lower estimates (Adamu et al, 2020;Sarma et al, 2020;Sowande et al, 2010;Thiruvenkadan, 2005) than in our study were also reported in different goat populations. Differences in estimates are attributed to genetic differences between breeds and variations in environments.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Highest value was obtained between BL and TL (r= 0.947; p<0.05), lowest value was obtained between HG and TL (r= 0.055; p>0.05). This result is similar with the report of Adamu et al (2020) who reported that coefficient values observed were in general high, positive and significant except between WH and TL in male and between BW and UC, BCS and BL, WH, UL and UC in female. He also reported that highest observed in this study when BW is predicted from HG conform the report of Tsegaye et al (2013) that this trait (HG) is positively correlated with live weight (LW) and can indicate it with high precision (R 2 = 0.94).…”
Section: Table: 3 General Phenotypic Correlation Coefficient Between Body Weight (Kg) and Body Linear Measurements (Cm) Forsupporting
confidence: 92%
“…In most agrarian African settings, ownership of livestock, especially goats, is a measure of social status, cultural heritage, and form of insurance against crop failure [1]. Consequently, various goat breeds-Sahel, Maradi, Red Sokoto, Kano brown and West African Dwarf (WAD)-are widely reared for production of meat, milk or skin in Africa [2][3][4][5]. In Nigeria, people often refer to the goat as the "cattle of the poor" because of its importance in the provision of animal protein and the farmers' economic wellbeing.…”
Section: Introductionmentioning
confidence: 99%